1994
DOI: 10.1007/bf00195769
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous, microscopic and lymphocytic colitis. An evolving concept

Abstract: Collagenous colitis and lymphocytic colitis (previously described as microscopic colitis) are two newly recognised forms of colitis. Both have generated much controversy and continue to do so; their aetiology and pathogenesis are unresolved and their association with a variety of immune-related disorders is intriguing. Response to available therapeutic modalities is often disappointing. The possible relationship or overlap between these two conditions remains a controversial issue. The aim of this review is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 43 publications
0
12
0
6
Order By: Relevance
“…The distribution and amount of surface IELs was too focal and mild to be categorized histologically as lymphocytic colitis. [2][3][4][5]7,8 Nevertheless, the features of the most heavily inflamed areas of these NSAID-associated colitis biopsies and those of lymphocytic colitis overlapped. NSAIDs have been linked to collagenous colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution and amount of surface IELs was too focal and mild to be categorized histologically as lymphocytic colitis. [2][3][4][5]7,8 Nevertheless, the features of the most heavily inflamed areas of these NSAID-associated colitis biopsies and those of lymphocytic colitis overlapped. NSAIDs have been linked to collagenous colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although not measured, a normal subsurface collagen layer thickness was defined as less than the thickened subsurface collagen band of collagenous colitis. [3][4][5][6][7][8][9] 9. Pericryptal fibroblastic sheath thickness, categorized as either normal or thickened.…”
Section: Methodsmentioning
confidence: 99%
“…The histologic findings of intraepithelial lymphocytic infiltrates and epithelial injury throughout the gastric and intestinal biopsy material and the serologic presence of several autoantibodies, including antigliadin, antiendomysial, and pANCA, are unifying features. Recently, reports have shown overlap of both related and seemingly (17,(21)(22)(23)(24)(25). Associated clinical and pathologic features of these chronic inflammatory bowel diseases suggest overlapping causes or a similar pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…All control cases were age-matched, and those classified as gastritis included seven cases that originally were diagnosed as chronic nonspecific gastritis, one case of chronic atrophic gastritis with intestinal metaplasia, and two cases of active chronic gastritis with Helicobacter pylori. Studies of the colon have indicated a collagen table thickness with an upper range of 3 to 7 as normal (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…First described in 1976 [9], and for a long time considered to be very rare, it has now become clear this is one of the main causes of chronic watery diarrhea in patients without or with unspecific (such as erythema and mucosal edema) endoscopic findings [5, 6, 10, 11, 12, 13, 14, 15]. Currently, the term microscopic colitis is used for all those conditions characterized by chronic watery diarrhea, with normal radiological and endoscopic appearances in the presence of microscopic changes [11, 16, 17, 18]. The term microscopic colitis includes the diagnoses collagenous colitis, lymphocytic colitis and eosinophilic colitis [16].…”
Section: Introductionmentioning
confidence: 99%